Successful treatment of a Candida auris intra-articular infection. Issue 1 (1st January 2019) - Roberts, Scott C.; Zembower, Teresa R.; Bolon, Maureen K.; Kadakia, Anish R.; Gilley, Jasen H.; Ko, Jason H.; Clark, Jessica; Ward-Fore, Sharon; Taiwo, Babafemi O.
ABSTRACT: A 78-year-old woman with a long-term ankle spacer with antibacterials developed an intra-articular Candida auris infection. Treatment with systemic antifungal therapy plus an amphotericin B moulded cement spacer was successful.